Safety and Efficacy of Magnetic Resonance-Guided Focused Ultrasound Surgery With Autofocusing Echo Imaging - Chang, Kyung Won; Rachmilevitch, Itay; Chang, Won Seok; Jung, Hyun Ho; Zadicario, Eyal; Prus, Oleg; Chang, Jin Woo (Frontiers in Neuroscience, 2021)
Objective: The skull, which is a major barrier of ultrasound sonication, is round but has an irregular surface and varies its size and shape among individuals. Recently, we developed the concept of skull density ratio (SDR) for the proper selection of the candidate of magnetic resonance guided focused ultrasound surgery (MRgFUS) lesioning for patients with essential tremor (ET). However, SDR alone is not the factor to guarantee the successful treatment of MRgFUS lesioning. Currently, the approach to refine the target by exact measurement of the ultrasonic echo in the transducer has been suggested to improve the efficacy of MRgFUS lesioning, we underwent MRgFUS lesioning with this autofocusing (AF) echo imaging technique. Methods: From Dec, 2019 to March, 2020, we recruited 10 patients (ET and PD) with low SDR, 2 patients dropped out of the trial due to screening failure of previous medical history. Total 8 patients were included and underwent MRgFUS thalamotomy in 6 patients with ET and MRgFUS pallidotomy in 2 patients with Parkinson’s disease (PD) with AF echo imaging technique. Results: The mean SDR of the patients with ET was 0.34 (range, 0.29-0.39) and patients with PD was 0.41 (range, 0.38-0.44). The mean skull volume of patients with ET was 280.57 (range, 227–319) cc and patients with PD was 287.13 (range 271-303) cc. During the MRgFUS, average of 15 sonication was performed among average of 5.63 were using AF technique. The mean maximal temperature (Tmax) achieved was 55.88 ℃ (range, 52-59) and the mean energy delivered was 34.75KJ (range 20~42) in patients with ET and PD. No serious adverse events occurred during and after the treatment. None of the sonication factors (Skull volume, SDR, sonication number, AF score, similarity score, Energy Range & Power) and Max Temperature was correlative with AF echo imaging technique (P>0.05, AF Score showed P=0.071). Conclusions: With AF echo imaging MRgFUS lesioning technique, safe and efficient treatment is available even for patients with low SDR, which could expand the MRgFUS lesioning indications to SDR < 0.4 for patients with ET and SDR < 0.45 for patients with PD.